Pengetahuan Ekologi Lokal Orang Dayak Kendawangan Siakaran Terhadap Wild Edibble Plants: Studi Etnobotani - Shafhira Putri, Deani Rizqy; Mulyanto, Dede; Supangkat, Budiawati (Universitas Lambung Mangkurat, 2026)
The Dayak Kendawangan Siakaran people of Randai Village possess knowledge of wild food plants, derived from their daily interactions with the environment and from knowledge passed down through generations. This research was conducted with the aim of preserving the local ecological knowledge of the Dayak Kendawangan Siakaran people regarding wild food plants through documentation and recording. Data were obtained through observation, interviews, and free listing.The obtained data was then analyzed using RFC calculations, with the aim of observing and measuring how widely a plant species is known within a community. The results showed 104 species of wild food plants, divided into 42 family groups. Within these family groups, the largest number of wild food plants known to the Dayak Kendawangan Siakaran people is Arecaceae. The most commonly used part is the fruit (50%). Most of the wild plants known to the Dayak Kendawangan Siakaran people originate from forests. However, currently, the amount of forest in Randai Village is starting to decline in its primary function due to deforestation. This poses a threat to the local ecological knowledge of the Dayak Kendawangan Siakaran people regarding wild food plants. Therefore, to maintain their knowledge of wild plants from these threats, the Dayak Kendawangan Siakaran people are using a method of transplanting wild food plants.